2017
DOI: 10.1007/s40744-017-0061-7
|View full text |Cite|
|
Sign up to set email alerts
|

Impact of Participation in the Adalimumab (Humira) Patient Support Program on Rheumatoid Arthritis Treatment Course: Results from the PASSION Study

Abstract: IntroductionPatients with rheumatoid arthritis (RA) who are treated with adalimumab (ADA) are offered a proprietary patient support program (PSP, AbbVie Care®). The main objective of this study was to examine the effectiveness of ADA on RA treatment course over time in the context of PSP utilization.MethodsPASSION was a 78-week post-marketing observational study of RA patients with an insufficient response to ≥1 DMARD newly initiating ADA in routine clinical care that was conducted in Europe, Israel, Mexico, P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
26
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 16 publications
2
26
0
1
Order By: Relevance
“…Our results are in line with those of Van den Bosch and colleagues [20] who previously Our study has several implications. The study results showed significant associations in improvements in patient-reported outcomes in patients with AS treated with ADA who participated in the AC-PSP, and who received tailored services in the form of continuous CCCs within 18 months.…”
Section: Discussionsupporting
confidence: 93%
“…Our results are in line with those of Van den Bosch and colleagues [20] who previously Our study has several implications. The study results showed significant associations in improvements in patient-reported outcomes in patients with AS treated with ADA who participated in the AC-PSP, and who received tailored services in the form of continuous CCCs within 18 months.…”
Section: Discussionsupporting
confidence: 93%
“…The annual estimated costs of each patient were $35238.8 while the direct cost accounted for 90.2% and the cost of medication accounted for 78.6%. There were significant differences in change of ASQoL (change,3.89 [95%CI, 3.06 to 4.71]; P<0.0001) and EQ-5D (change, -0.19 [95%CI, -0.24 to -0.31]; P<0.0001) scores from baseline and 24 weeks, with more improvements after therapy compared with baseline. Cost of illness was The cost of AS patients treated with adalimumab therapy was high in China and symptoms and QoL improved significantly after therapy.…”
mentioning
confidence: 98%
“…Background: The diagnosis of rheumatoid arthritis (RA) using EULAR criteria through conventional assessments remains controversial, especially for those with seronegative results, many of patients without other diagnostic aids as imaging, could be wrong diagnosed followed by expensive treatments (1)(2)(3). Objectives: To evidence through real-world data how the use of imaging within a screening process of diagnosis of RA can saving future costs for unnecessary treatments in patients with misdiagnosis of RA.…”
mentioning
confidence: 99%
“…The annual estimated costs of each patient were $35238.8 while the direct cost accounted for 90.2% and the cost of medication accounted for 78.6%. There were significant differences in change of ASQoL (change, 3 Background: Adherence to therapy in chronic diseases such as inflammatory rheumatic diseases (CIRD), inflammatory bowel diseases (IBD) and psoriasis (Pso) is a major condition to achieve positive outcomes. Patient support programs (PSPs) were developed to improve the quality of care and enhance adherence to therapy.…”
mentioning
confidence: 99%